Screening and Production Study of Microbial Xylanase Producers from Brazilian Cerrado - Alves-Prado, Heloiza Ferreira [UNESP]; Pavezzi, Fabiana Carina [UNESP]; Ribeiro Leite, Rodrigo Simoes; de Oliveira, Valeria Maia; Sette, Lara Duraes; DaSilva, Roberto [UNESP] (Humana Press Inc, 2010)
Hemicelluloses are polysaccharides of low molecular weight containing 100 to 200 glycosidic residues. In plants, the xylans or the hemicelluloses are situated between the lignin and the collection of cellulose fibers underneath. The xylan is the most common hemicellulosic polysaccharide in cell walls of land plants, comprising a backbone of xylose residues linked by beta-1,4-glycosidic bonds. So, xylanolytic enzymes from microorganism have attracted a great deal of attention in the last decade, particularly because of their biotechnological characteristics in various industrial processes, related to food, feed, ethanol, pulp, and paper industries. A microbial screening of xylanase producer was carried out in Brazilian Cerrado area in Selviria city, Mato Grosso do Sul State, Brazil. About 50 bacterial strains and 15 fungal strains were isolated from soil sample at 35 A degrees C. Between these isolated microorganisms, a bacterium Lysinibacillus sp. and a fungus Neosartorya spinosa as good xylanase producers were identified. Based on identification processes, Lysinibacillus sp. is a new species and the xylanase production by this bacterial genus was not reported yet. Similarly, it has not reported about xylanase production from N. spinosa. The bacterial strain P5B1 identified as Lysinibacillus sp. was cultivated on submerged fermentation using as substrate xylan, wheat bran, corn straw, corncob, and sugar cane bagasse. Corn straw and wheat bran show a good xylanase activity after 72 h of fermentation. A fungus identified as N. spinosa (strain P2D16) was cultivated on solid-state fermentation using as substrate source wheat bran, wheat bran plus sawdust, corn straw, corncob, cassava bran, and sugar cane bagasse. Wheat bran and corncobs show the better xylanase production after 72 h of fermentation. Both crude xylanases were characterized and a bacterial xylanase shows optimum pH for enzyme activity at 6.0, whereas a fungal xylanase has optimum pH at 5.0-5.5. They were stable in the pH range 5.0-10.0 and 5.5-8.5 for bacterial and fungal xylanase, respectively. The optimum temperatures were 55C and 60 A degrees C for bacterial and fungal xylanase, respectively, and they were thermally stable up to 50 A degrees C.
Keywords: Microbial enzyme; Xylanase; Brazilian cerrado; Lysinibacillus sp.; Neosartorya spinosa